Optimum Welfare and Maximum Revenue Tariffs - Johnson, Harry G. (Review of Economic Studies, 1951)
Journal Article Optimum Welfare and Maximum Revenue Tariffs Get access Harry G. Johnson Harry G. Johnson Cambridge Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 19, Issue 1, 1950, Pages 28–35, https://doi.org/10.2307/2296268 Published: 01 December 1950